Oral health care in the Núcleo Educacional Fiores community - Sales, Aline; Martins, Rayssa; Casseb, Tamiris; Júnior, Aluisio Celestino; Alexandre, Jordana (Guará Journal, 2016)
The aim of this paper was to describe the educational and preventive actions on oral health carried out in the school community in the city of Benevides in Para State, Brazil. Directly they were met 196 children. Lectures were held, workshops, games interatives, group dynamics, design and figures for reading and coloring. Also it was conducted epidemiological survey of caries in addition to brushing orientation of the teeth, flossing instruction and topical fluoride application; these actionscontributed to better understanding of risk factors and illness on the main diseases of mouth. Atraumatic Restorative TreatmentART were performed in children who had cavities. Conducting outreach activities carried out school contribute significantly to dental care from the perspective of prevention but also as a learning opportunity to dental students.
Keywords: Oral health; Education; Prevention; Experience report